A study of active components in aloe vera barbadensis extract using soxhlet extraction method - Chong, An Ting (2020)
Aloe Vera is the oldest medicinal plant ever known and used in cosmetics from centuries worldwide. The active components extracted from Aloe Vera Barbadensis is useful to solve the skin problems and replace the insecure chemical ingredients that used in cosmetic application. The objectives of this study are (1) to extract the active components from Aloe Vera plant using soxhlet extraction method; (2) to investigate the presence of active components from different part of Aloe Vera extract by using different type of solvents and; (3) to determine the concentration of phenolic and flavonoid contents in Aloe Vera extracts. The Aloe Vera gel and root samples were extracted by using soxhlet extraction method with different type of solvents. The presence of active components of the extracts were analysed by using FTIR. The Aloe Vera extracts were used to test for the presence of carbohydrate, steroid, anthraquinone and tannin components. The total phenolic and flavonoid contents were determined by using UV-Vis spectrophotometer. The total phenolic content of the extracts were determined by using Folin-Ciocalteu reagent and gallic acid as standard. The total flavonoid contents were determined by using aluminium chloride colorimetric method and used quercetin as standard. Most of the Aloe Vera extracts shown the presence of steroids and tannins components. The number of absorption peak that observed in ethanolic extracts are more than in methanolic and aqueous extracts. The highest total phenolic and flavonoid contents were found in aloe vera root ethanolic extracts as compared with other solvent extracts with the value of 0.5502 mg/mL and 0.3685 mg/mL respectively. The Aloe Vera root extracts show the higher concentration of phenolic and flavonoid content which may possess a higher antioxidant activity as compared with Aloe Vera gel extracts. Therefore, it could exploit to a new field of research in cosmetic application in the future.